Protection of Arabidopsis Blunt-Ended Telomeres Is Mediated by a Physical Association with the Ku Heterodimer. Issue 6 (5th June 2017) - Valuchova, Sona; Fulnecek, Jaroslav; Prokop, Zbynek; Stolt-Bergner, Peggy; Janouskova, Eliska; Hofr, Ctirad; Riha, Karel
Abstract : Chromosome ends are sequestered from aberrant DNA repair activities within the DNA binding channel of the Ku heterodimer. Abstract: Telomeres form specialized chromatin that protects natural chromosome termini from being recognized as DNA double-strand breaks. Plants possess unusual blunt-ended telomeres that are unable to form t-loops or complex with single-strand DNA binding proteins, raising the question of the mechanism behind their protection. We have previously suggested that blunt-ended telomeres in Arabidopsis thaliana are protected by Ku, a DNA repair factor with a high affinity for DNA ends. In nonhomologous end joining, Ku loads onto broken DNA via a channel consisting of positively charged amino acids. Here, we demonstrate that while association of Ku with plant telomeres also depends on this channel, Ku's requirements for DNA binding differ between DNA repair and telomere protection. We show that a Ku complex proficient in DNA loading but impaired in translocation along DNA is able to protect blunt-ended telomeres but is deficient in DNA repair. This suggests that Ku physically sequesters blunt-ended telomeres within its DNA binding channel, shielding them from other DNA repair machineries.